Enzyme Inhibitory Kinetics and Molecular Docking Studies of Halo-Substituted Mixed Ester/Amide-Based Derivatives as Jack Bean Urease Inhibitors. (24th December 2020) - Rashid, Muhammad; Rafique, Hummera; Roshan, Sadia; Shamas, Shazia; Iqbal, Zafar; Ashraf, Zaman; Abbas, Qamar; Hassan, Mubashir; Qureshi, Zia Ur Rahman; Asad, Muhammad Hassham Hassan Bin
Abstract : A series of halo-substituted mixed ester/amide-based analogues 4a-l have been prepared as jack bean urease inhibitor, which showed good to excellent inhibition of enzyme activity. The role of halo-substituted benzoyl moieties and alkyl substituted anilines in urease inhibitory kinetics was also investigated. The alkyl-substituted anilines 1a–b reacted with chloroacetyl chloride to afford intermediates 2a-b, which were then reacted with different halo-substituted benzoic acids 3a–f to prepare the title compounds 4a-l . The chemical structures of final products 4a-l were ascertained by FTIR, 1 H NMR, 13 C NMR, and mass spectra. The compound 4b showed remarkable activity with IC50 1.6 ± 0.2  nM, better than the standard thiourea having IC50 472.1 ± 135.1  nM. The 2-chloro-substituted phenyl ring on one side of compound 4b and 4-isopropyl-substituted benzene on the other side play an essential role in inhibition of urease activity. Lineweaver–Burk plots (kinetics study) indicated about 4b derivative as a mixed type of inhibitor. The virtual screening performed against urease enzyme (PDBID 4H9M) showed that compounds 4b and 4e have binding energies of −7.8 and −7.9 Kcal/mol, respectively. Based upon our results, it was found that derivative 4b is a highly potent urease inhibitor, better than the standard thiourea.